On System-Internal and Differential Iconicity in Egyptian Hieroglyphic Writing - Andréas Stauder (Signata, 2018)
While referential modes of iconicity in signs of writing are well recognized, this paper emphasizes the complementary importance of system-internal modes of iconicity and sign motivation in complex writing systems. Focusing on Egyptian hieroglyphs particularly, instances of differential iconicity are discussed, by which the very differences between pairs or small sets of visual related signs are essential in motivating these. In some cases, it is proposed, differential iconicity affords the foundation for referential modes of iconicity themselves.